Cerebrotendinous xanthomatosis: Clinical and neuroimaging findings - S Sheetal (Archives of Medicine and Health Sciences, 2020)
Cerebrotendinous xanthomatosis (CTX) is a rare autosomal recessive disorder of effective bile acid biosynthesis (adult lipid storage disorder with the underlying mutation in the CYP27 gene, which encodes sterol 27-hydroxylase, a key enzyme in the conversion of cholesterol to the primary bile acids cholic and chenodeoxycholic acid). Hereby, we report the case of a 39-year-old male who presented with progressive walking difficulty, ataxia, and cognitive decline since childhood, who had cataract and tendon xanthomas on examination. Magnetic resonance imaging of the brain showed typical bilateral and symmetrical involvement of the dentate nuclei, characteristic of CTX.